Bimasakti menari - Sri Rahayu Mohd Yusop (Kuala Lumpur : Utusan Publications & Distributors, 2011)
Prize winning novel in the 2010 juvenile novel writing contest of Kumpulan Utusan.
Novel.
In Malay.
Keywords: Science fiction, Malay; Young adult fiction, Malay; Malay fiction -- 21st century